Water-stress-induced changes in resin and rubber concentration and distribution in greenhouse-grown guayule - Veatch-Blohm Maren E; McCloskey William B; Ray Dennia T (Agronomy Journal, 2006)
Guayule (Parthenium argentatum A. Gray) is naturally subject to periods of water stress in its native habitat. It has been shown that, under cultivation, rubber yield increase with increasing irrigation, but rubber concentration per plant decreases. The effect of irrigation on resin concentration is unclear. The purpose of this study was to understand how resin concentration is affected by water stress, and why water stress increases rubber concentration. Greenhouse-grown guayule plants were subjected to water stress in four experiments, each of 3 mo duration. Two experiments were conducted in the summer, the active growth period, and two experiments were conducted in the winter. The water-stressed plants were irrigated when the average soil water potential reached either -0.6 MPa (first summer experiment) or - 0.3 MPa (all subsequent experiments). Water-stress effects were monitored by measuring growth, C exchange, biomass, and resin and rubber production. Water-stressed plants had lower C exchange, growth, and leaf-to-stem ratio than well-watered plants. Resin concentration did not respond consistently to water stress. Rubber concentration was generally higher in the water-stresses plants than in the well-watered plants as a result of decreased leaf biomass in both the summer (33 vs 45 g kg -1) and winter (36 vs. 52 g kg -1) and decreased stem diameter in the summer (8.1 vs. 11.0 mm). Rubber is deposited mainly in the bark; therefore, reduced leaf biomass and stem diameter contribute to higher rubber concentration in the water-stressed plants by increasing the relative amount of bark.
Keywords: Guayule; Rubber concentration